DESIGN VIDEO COURSE LEARNING HIGH SCHOOL MATHEMATICS WITH FLIPPED CLASSROOM MODEL FOR IMPROVING STUDENTS' CRITICAL THINKING ABILITY - Nurmawati Nurmawati; Ismartoyo Ismartoyo; Eem Kurniasih (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
During the current pandemic, students have difficulty understanding mathematical material, usually they are taught by lecturers face-to-face and now bravely, the obstacle experienced by students is that they feel that their learning is not optimal because often the signal is not good and is not stable enough to not be able to meet the lecturer. , to reduce this problem, it is necessary to make a video of learning material that will be delivered by a mathematics lecturer made by the teaching lecturer, the video is placed on youtube and the youtube link is given to students to study first for the upcoming meeting, this is in accordance with the flipped classroom model where students are asked to study first the videos made by their lecturers before being explained directly by the lecturers, it is hoped that students are able to think creatively about the video material made by their lecturers and students are able to analyze the lack of material that they have not understood n is explained by the lecturer at the next meeting, while the research method used is using the ADDIE R & D model (Analysis, Design, Develop, Implementation and Evaluation), The research subjects were college students of mathematic education program of Open University. The sampling technique used was purposive sampling. The results of this study are design of learning video with flipped classroom model with material expert validation results with a feasibility percentage of 92% and media expert validation results of 93% with very good criteria. Thus, this product is is very suitable to be used as a supplement to lecture material at open universities, especially high school mathematics curricular subjects and make college student improve critical thinking in the class and the results of this study using a one-sided t-test showed or 2,097 > 1,674 so that the average learning outcomes of the experimental class using learning videos were better than the average learning outcomes of the control class without using learning videos as learning supplements; of student responses that is 88.4% in the very good category.